Neil Buttery, Before Mrs Beeton, Elizabeth Raffald, England’s Most Influential Housekeeper - Bainbridge, Fay (Petits Propos Culinaires, 2023)
Neil Buttery, Before Mrs Beeton, Elizabeth Raffald, England’s Most Influential Housekeeper: Pen & Sword, 2023: 201pp., hardback, £20.